A Case Report on Escitalopram-Induced Hyperglycaemia in a Diabetic Patient. (August 2013) - Zuccoli, M. L.; Brasesco, P. C.; Milano, G.; Martelli, A.; Leone, S.; Mattioli, F.; Fucile, C.
The incidence of depression in diabetic patients is quite high; moreover, it has been suggested that the presence of depression itself may increase the risk of diabetes mellitus. Hence, it follows that the simultaneous use of antidiabetic and antidepressant drugs is common. Some clinical evidence indicates that selective serotonin re-uptake inhibitors (SSRIs) could be very useful in treating overweight patients, both with and without diabetes. However, recent deregulation of glucidic metabolism was tested in diabetic subjects treated with antidepressants. Several cases of hyperglycaemia and hypoglycaemia associated with other SSRIs have been published, whereas only one case of escitalopram inducing hyperglycaemia has been noted. The exact mechanism of glucose control impairment in patients taking SSRIs—escitalopram in particular—still remains unclear. We describe a diabetic 83-year-old woman with good glycaemic control (as evinced by glycaemic and glycosylated haemoglobin assay—HbA1c—values) before escitalopram initiation in response to therapy with glibenclamide. Escitalopram resulted in a significantly increased glycaemia values 5 days following administration. Glycaemia values returned to normality only after suspension of escitalopram, despite antidiabetic dosage increase. We report this case to draw attention to escitalopram as a possible cause of glycaemic control loss.